2013
DOI: 10.1103/physrevb.87.035440
|View full text |Cite
|
Sign up to set email alerts
|

Role of charge transfer, dipole-dipole interactions, and electrostatics in Fermi-level pinning at a molecular heterojunction on a metal surface

Abstract: Recently, Niederhausen et al. [Phys. Rev. B 86, 081411(R) (2012)] have reported on the energy level alignment of C 60 adsorbed on a bilayer α-sexithiophene (6T) film on Ag(111). The possibility of charge transfer from the metal to the C 60 through the bilayer 6T as discussed by the authors may have a strong impact on understanding the energy level alignment (ELA) at organic-organic (O-O) heterojunctions grown on electrodes. In this paper, we aim at a comprehensive picture of the ELA at O-O interfaces on a meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
73
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 66 publications
12
73
0
Order By: Relevance
“…[ 20 ] Koch and co-workers have recently shown that there is clear electron injection from alkali halideand sexithiophene-modifi ed Ag electrodes that are in contact with C 60 . [ 3,21,22 ] Here, we demonstrate for the fi rst time that these anionic hybridized interfacial gap states that are formed at alkali metal hydroxide-modifi ed AZO contacts result in dramatically enhanced performance for bulk heterojunction solar cells composed of a pDPP5T-2:PC 61 BM blend.…”
Section: Introductionmentioning
confidence: 95%
“…[ 20 ] Koch and co-workers have recently shown that there is clear electron injection from alkali halideand sexithiophene-modifi ed Ag electrodes that are in contact with C 60 . [ 3,21,22 ] Here, we demonstrate for the fi rst time that these anionic hybridized interfacial gap states that are formed at alkali metal hydroxide-modifi ed AZO contacts result in dramatically enhanced performance for bulk heterojunction solar cells composed of a pDPP5T-2:PC 61 BM blend.…”
Section: Introductionmentioning
confidence: 95%
“…[ 31 ] Conversely C 60 fullerene is a standard choice as n-type semiconductor either used as such in its crystalline form or, more often, functionalized to make it soluble and polar as the widely used PCBM which is most often amorphous. The T6-C 60 interface has been studied with ultraviolet and X-ray photoelectron spectroscopy to assess Fermi level alignment and the extent of charge transfer, [32][33][34] as it constitutes a prototypical system for solar cells. [35][36][37] In addition, it has been shown that the relative weak intermolecular interactions at this interface can be exploited and controlled in order to achieve a variety complex architectures.…”
Section: Introductionmentioning
confidence: 99%
“…25−28 For the same configuration on Ag substrates, a charge transfer from the substrate directly to the C 60 through the neutral 6T has been reported. 29,30 For 6T OPV cells using the PHJ geometry, an extraordinarily high open-circuit voltage, utilizing DIP (Figure 1 right) as electron-acceptor material, is reported. 20 In contrast with the sphere-like C 60 , the perylene derivate DIP is rod-like and hence sterically more compatible to 6T.…”
Section: ■ Introductionmentioning
confidence: 98%